HUBUNGAN ANTARA KONSENTRASI SISWA DENGAN KETEPATAN PASSING BAWAH DALAM PERMAINAN BOLAVOLI (STUDI PADA SISWA KELAS X JURUSAN ADMINISTRASI PERKANTORAN SMK NEGERI 1 BOYOLANGU TULUNGAGUNG TAHUN AJARAN 2012/2013) - HARI NURCAHYONO, FEBRI (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract In order to be able for students to perform low-passing in the volleyball game well and fit the aimed target, a teacher who especially teaches volleyball students X class must create an atmosphere in order the students are able to concentrate properly. This study aimed to determine: 1) To know is there any relationship between the concentration of students with an accuracy level of low passing in the volleyball game. 2) To know how big the contribution of the concentration level to the accuracy of down-passing volleyball game. Sample of this study are students X AP 2 class at SMK Negeri 1 Boyolangu Tulungagung periode 2012/2013 totaling 43 students consist of 1 boy and 42 girls, using purposive sampling techniques totally from student class X population of SMK Negeri 1 Boyolangu. Type of the research to be used is quantitative descriptive correlational type with the design of cause and effect relationship. Based on the calculation of data analysis, it gets the value ??of rcalculation is bigger than rtable (0,654 > 0,361), which means there is a significant correlation between the students’ concentration to the accuracy of volleyball down-passing. The number of relationship between the students’ concentration levels to the accuracy of down-passing is 42,77%. It can be concluded that there is a relationship between the students’ concentration level with the accuracy of low passing in volleyball game to the students X class. The higher the students’ concentration level, the higher the students’ accuracy of low passing will be. Keywords : the relationship, students’concentration, the accuracy of down-passing